Significance of pleural effusion detected by metagenomic next-generation sequencing in the diagnosis of aspiration pneumonia - Zhu, Ling; Hao, Yuqiu; Li, Wei; Shi, Bingqing; Dong, Hongna; Gao, Peng (Frontiers in Cellular and Infection Microbiology, 2022)
Objective Using metagenomic next-generation sequencing (mNGS) to profile the bacterial pathogen of pleural infection in aspiration pneumonia for therapeutic decision-making. Methods Collection and analysis of the clinical and laboratory data of aspiration pneumonia patients who underwent mNGS detection of pleural effusion at the Second Hospital of Jilin University from November 2020 and March 2022. Results Nine males and one female were included, aged 33 to 69 years. All patients had chest pain, fever, cough, and hypoxemia symptoms; 90% had expectoration. The laboratory tests revealed that all patients had elevated white blood cell, neutrophil, and C-reactive protein (CRP) levels. Furthermore, erythrocyte sedimentation rate (ESR) increased in 8 patients, and procalcitonin increased in only one patient. Chest CT indicated different degrees of lobar pneumonia and pleural effusion in all patients, and biochemical results implied exudative effusion according to Light criteria. Most routine culture results were negative. Among bacteria identified by mNGS, Fusobacterium nucleatum (n=9) was the most common, followed by Parvimonas micra (n=7) and Filifactor alocis (n=6). Three patients underwent surgical treatment after applying targeted antibiotics, thoracic puncture and drainage, and fibrinolytic septum treatment. After the adjusted treatment, the number of white blood cells, neutrophils, and lymphocytes decreased significantly, indicating the eradication of the infection. Conclusions Improving the vigilance of atypical people suffering from aspiration pneumonia is essential. The mNGS detection of pleural effusion clarified the microbial spectrum of aspiration pneumonia, allowing targeted antibiotic administration.